# Solve by substitution

Anonymous
account_balance_wallet \$5

### Question Description

calebrite
School: University of Maryland

we start by making c the subject of the first equation

c=6-a-b

we substitute this value of c into the other equations

2a-b+(6-a-b)=3 =>  a-2b=-3 .....4

3a-b+(6-a-b)=4 => 2a-2b=-2 .....5

making a the subject of equation 4;

a=2b-3

substituting a into equation 5;

2(2b-3)-2b =-2 => 2b=4

b=2

a=2b-3; a=2(2)-3;

a=1

a+b+c =6

1+2+c=6 => c=6-3

c=3

flag Report DMCA
Review

Anonymous
Top quality work from this guy! I'll be back!

Brown University

1271 Tutors

California Institute of Technology

2131 Tutors

Carnegie Mellon University

982 Tutors

Columbia University

1256 Tutors

Dartmouth University

2113 Tutors

Emory University

2279 Tutors

Harvard University

599 Tutors

Massachusetts Institute of Technology

2319 Tutors

New York University

1645 Tutors

Notre Dam University

1911 Tutors

Oklahoma University

2122 Tutors

Pennsylvania State University

932 Tutors

Princeton University

1211 Tutors

Stanford University

983 Tutors

University of California

1282 Tutors

Oxford University

123 Tutors

Yale University

2325 Tutors